The male of the species: a profile of men in nursing. (22nd January 2016) - Stanley, David; Beament, Tania; Falconer, Darren; Haigh, Margaret; Saunders, Rosemary; Stanley, Karen; Wall, Peter; Nielson, Sharon
Abstract: Aim: To establish a profile of men in nursing in Western Australia and explore the perception of men in nursing from the perspective of male and female nurses. Background: A project team, including some of the current authors, produced a YouTube video and DVD about men in nursing which led to further enquiry on this topic. Design: The study employed a non‐experimental, comparative, descriptive research design focused on a quantitative methodology, using an online survey in early 2014. Method: A convenience sample incorporated registered and enrolled nurses and midwives in Western Australia. Findings: The range of data included demographic information and the respondents' perceptions of men in nursing were collected. Findings indicated that the main reasons for choosing a career in nursing or midwifery were similar for both genders. Common mis‐perceptions of men in nursing included: most male nurses are gay; men are not suited to nursing and men are less caring and compassionate than women. Suggestions to promote nursing to men included: nurses are highly skilled professionals; there is the potential to make a difference for patients; nursing offers stable employment, professional diversity and opportunities for team work. There is a diminished awareness of opportunities for men in nursing and negative stereotypes related to men in nursing persist. Conclusion: The study produced recommendations which included: using the right message to target the recruitment for men and promoting a more realistic understanding of the profile and perception of men in nursing.